(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Speech Recognition is a technology which allows the processing of a speech input to text and is speaker independent. This allows it to be used in numerous applications ranging from digital assistants to controlling machinery. This paper proposes a strategy which can be used in controlling a robotic vehicle through connected speech input. The speech recognizer platform will be an Android smartphone which communicates with the robot using Bluetooth Connectivity. This method allows for efficient recognition and smooth data transfer. Additionally the robot will also have the capability to detect obstacles and inform the user to use a different command. Our proposed technique will be useful for applications such as assistive robots for people with disabilities or in industrial applications such as work robots